The Use of Videos in Improving Middle School Students' Understanding Based on Their Learning Styles During the Covid-19 Pandemic - Nurdin Kaso; Dodi Ilham; Muhammad Iksan; Andi Muhammad Ajigoena; Nurul Aswar; Hisbullah Nurdin (Universitas Negeri Makassar, 2023)
This study aims to determine students' visual, auditory, and kinesthetic understanding after learning to use PAI learning videos for jama' and qasar prayers for 7th-grade students of Junior High School (SMP Negeri 3 Makassar). This type of research uses a mixed approach (mix method). The research data is divided into primary data and secondary data. Data collection techniques used are questionnaires, tests, observations, documentation, and interviews. The research instrument was a learning style questionnaire, comprehension test, interview guide, observation guide, and documentation. Checking the validity of the data using triangulation techniques or methods. Data analysis through the process of data reduction, categorization, and synthesis. The results showed that students who had (1) a visual learning style met the indicators of re-explaining, interpreting, classifying, compare and concluding well. Meanwhile, the ability to give examples and applications is still not fulfilled. The results of understanding achieved are influenced by the ability of the eye to see information in the learning video. (2) auditory learning style fulfills the re-explaining, interpreting, classifying, and comparing indicators. Meanwhile, giving examples, concluding, and applying is still not fulfilled. The result of understanding achieved is influenced by the ability of the sharpness of the ear to listen to the explanation of the information in the learning video. (3) the kinesthetic learning style meets the indicators of the ability to re-explain, classify, compare and conclude. while the ability to interpret, give examples and applications is still not fulfilled